2007
DOI: 10.1186/1465-9921-8-27
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of MAP kinase pathways after maternal IL-1β exposure induces fetal lung fluid absorption in guinea pigs

Abstract: Background: We tested the hypothesis that maternal interleukin-1β (IL-1β) pretreatment and induction of fetal cortisol synthesis activates MAP kinases and thereby affects lung fluid absorption in preterm guinea pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In some studies, dopamine and isoproterenol as well as growth factors up-regulate Na,K-ATPase expression via activating MEK and ERK [15,19,20]. In our earlier study [16], MEK and ERK activation did not change lung ENaC expression, but stimulated lung fluid absorption in fetal guinea pigs. It has been suggested that MAP kinase activation during high V t ventilation leads to type II cell hyperplasia [40].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In some studies, dopamine and isoproterenol as well as growth factors up-regulate Na,K-ATPase expression via activating MEK and ERK [15,19,20]. In our earlier study [16], MEK and ERK activation did not change lung ENaC expression, but stimulated lung fluid absorption in fetal guinea pigs. It has been suggested that MAP kinase activation during high V t ventilation leads to type II cell hyperplasia [40].…”
Section: Discussionmentioning
confidence: 92%
“…We [16] and others [15,19] have shown that these proteins can be important for lung fluid absorption. In some studies, dopamine and isoproterenol as well as growth factors up-regulate Na,K-ATPase expression via activating MEK and ERK [15,19,20].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has also been demonstrated that stretch‐induced release of MAP kinases may be involved in regulating fetal lung fluid absorption (Koshy et al, in press). MAP kinases have, in several studies, been proposed to regulate lung fluid absorption in both positive and negative ways (Pesce et al, 2000; Guerrero et al, 2001; Frank et al, 2003; Upadhyay et al, 2003; Lin et al, 2005; Roux et al, 2005; Bhattacharjee et al, 2007).…”
Section: Discussionmentioning
confidence: 99%